After-Sight (with Longchenpa). Issue 2 (4th May 2019) - Chung, Una
ABSTRACT: Longchen Rabjam or Longchenpa (1308–1364) was a Buddhist practitioner, teacher, and spiritual leader in the Nyingma lineage in Tibet. He is a prominent figure associated with Dzogchen and is credited with both synthesizing and clarifying its essential teachings. Dzogchen's concern with the category of experience, and in particular a kind of direct perception that points to non-reified vision, presents an intriguing problem for contemporary studies of art and culture.